2020
DOI: 10.2147/ccid.s229054
|View full text |Cite
|
Sign up to set email alerts
|

<p>Polycaprolactone: How a Well-Known and Futuristic Polymer Has Become an Innovative Collagen-Stimulator in Esthetics</p>

Abstract: Compared to other domains, tissue engineering and esthetics have dramatically expanded in recent years, leading to both major biomedical advances and futuristic perspectives. The two share a common approach based on biomaterials, especially polymers. This paper illustrates this with the example of polycaprolactone (PCL), a polymer synthesized in the early 1930s, and one of its most recent applications, a PCL-based collagen stimulator, a filler used in esthetics. PCL is biocompatible and biodegradable. Its spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 122 publications
3
70
0
1
Order By: Relevance
“…Safety was followed up for 30 months in a recent European multicenter clinical trial involving 90 subjects. These studies were detailed in a recent review 4 . Several publications dealing specifically with PCL filler complications have also indicated that the product shows high safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety was followed up for 30 months in a recent European multicenter clinical trial involving 90 subjects. These studies were detailed in a recent review 4 . Several publications dealing specifically with PCL filler complications have also indicated that the product shows high safety.…”
Section: Discussionmentioning
confidence: 99%
“…In one analysis of cases induced by dermal fillers, one case of xanthelasma‐like reaction using PCL‐based filler was cited, showing that this is an extremely rare reaction 22 . Physicians must be able to properly manage adverse events, should they occur; in this regard, treatment guidelines for PCL‐based filler have been recommended by experts 4 . To date, there is no effective method of product removal, so prevention is the best solution to avoid adverse events, as with any dermal fillers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG has been widely utilized in biomedical applications, such as bioconjugation, in which it is either directly conjugated with drugs or attached to the surface of drug-encapsulating nanomaterials (a technique known as PEGylation) [ 95 ], in drug delivery [ 96 ], in biosensing (e.g., for electrochemical, optical and mass-based biosensors) [ 97 ], and in tissue engineering [ 98 ]. PCL has recently been considered for biomedical applications, including bone tissue engineering [ 99 ], drug delivery [ 100 ], and as dermal and subdermal fillers, since it is an excellent collagen stimulator [ 101 ]. The other attractive polymer for the fabrication of drug delivery and tissue engineering applications is PLGA [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications include scaffolds for bone defects in craniomaxillofacial surgery and fillers/threads in aesthetic facial rejuvenation. 7 Polycaprolactone is 3D printed and can be made accordingly to the shape desired. The dimension and strength can be varied as requested.…”
Section: What Is Polycaprolactone?mentioning
confidence: 99%